Field Measurement and Numerical Simulation of Sound Insulation Characteristics of Buildings Along Elevated Urban Rail Lines - Teng Wang; Wei He; Dongyang Wang; Jialiang Chen (Buildings)
The noise pollution issue along elevated urban rail transit lines has attracted considerable attention; however, research on the sound insulation characteristics of buildings during operational train noise remains limited. In this study, a field testing campaign was conducted in a building featuring facades constructed from aerated concrete blocks embedded with single-layer glass sliding windows along an elevated rail transit line. The sound insulation characteristics of the building were obtained based on measured data. By neglecting the influence of lateral sound transmission, a window-wall assembly model was proposed for simulating the building’s sound insulation capability. To ensure the accuracy of the prediction results, initial simulations were first performed on individual elements and compared against the experimental sound insulation curves to identify key parameters. Subsequently, simulations of the window-wall assembly model were carried out and compared with test data to determine the acoustic boundary treatment. The results showed that the amount of sound insulation measured in the buildings ranged from 11.16 dB (A) to 19.85 dB (A) during train passage, exhibiting a notable dip in sound insulation within the frequency range of 80 Hz to 100 Hz. Conversely, the predicted sound insulation of 26.38 dB was much higher, also showing a significant dip at around 100 Hz. The simulated values aligned closely with the measured values below 500 Hz; however, discrepancies were observed in mid-to-high frequency ranges above this threshold. To this end, further simulations were performed on a window-wall assembly model incorporating air gaps to take into account air leakage effects. The results indicated that the presence of air gaps considerably diminished high-frequency sound insulation; when accounting for window air leakage effects, the simulated results approached closer alignment with the measured ones.